2010
DOI: 10.11606/issn.1679-9836.v89i2p76-82
|View full text |Cite
|
Sign up to set email alerts
|

Fatores relacionados ao tabagismo e ao seu abandono

Abstract: Objetivo: Verificar a prevalência do hábito de fumar em um grupo profissional e evidenciar quais fatores estão relacionados ao tabagismo e ao seu abandono. Casuística e Método: Foram avaliados, prospectivamente, 494 funcionários da Procuradoria Geral de Justiça de Minas Gerais, na cidade de Belo Horizonte, consecutivos e aleatoriamente incluídos, de um total de 1229 pessoas. Eles responderam a questionário relacionado ao tabagismo, com vista à avaliação de fumantes, não-fumantes e ex-fumantes. Foram incluídas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
(28 reference statements)
0
4
0
6
Order By: Relevance
“…The lower proportion of smokers among teachers with sufficient physical activity can be interpreted as an expected gain among those that have already manifested better adherence to healthy habits. In other words, it is consistent with adherence to physical activity to be less prone to unhealthy habits such as tobacco consumption 38 .…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The lower proportion of smokers among teachers with sufficient physical activity can be interpreted as an expected gain among those that have already manifested better adherence to healthy habits. In other words, it is consistent with adherence to physical activity to be less prone to unhealthy habits such as tobacco consumption 38 .…”
Section: Discussionmentioning
confidence: 53%
“…Saúde Pública 2019; 35 Sup 1:e00180217 "life's journey", thereby constituting a barrier to recourse to negative coping strategies like substance use. The family exerts a well-documented influence on the success of smoking cessation strategies 38 .…”
Section: Discussionmentioning
confidence: 99%
“…The results demonstrated that the presence of a trigger, understood as a factor that motivates smoking, acts as a deterrent to smoking cessation because it predisposes to relapse. According to Cardoso et al 6 (2010), the occurrence of relapse is correlated with sociodemographic variables and the level of addiction; the present study evaluated whether the presence or absence of triggers in the face of relapse was associated with patient status at the end of treatment.…”
Section: Discussionmentioning
confidence: 95%
“…Em relação à associação tabagismo e álcool, verificou-se maior proporção de fumantes entre aqueles que relataram consumo abusivo de bebida alcoólica, além disso, mais da metade dos ex-fumantes que apresentaram CAGE positivo quando fumavam foi atualmente classificada como CAGE negativo, o que vai ao encontro do conhecimento a respeito dessa associação 20,29 . Chiolero et al 30 comentam que o uso de álcool e tabaco pode estar relacionado de duas maneiras: ligação intrapessoal, em que consumidores de álcool geralmente fumam e vice-versa; e ligação situacional, em que pessoas que usam álcool e tabaco podem usá-los juntos nas mesmas situações 31 .…”
Section: Discussionunclassified